15q23 Gain in a Neonate with a Giant Omphalocele and Multiple Co-Occurring Anomalies. (13th November 2018) - Zhou, Hui-Fang; O'Conor, Christopher J.; Gangahar, Chiraag; Dehner, Louis P.
Abstract : Background . Omphalocele is a rare congenital abdominal wall defect. It is frequently associated with genetic abnormality and other congenital anomalies, although isolated omphalocele cases do exist. Data have shown that omphalocele with co-occurring genetic abnormality has worse prognosis than isolated omphalocele. Chromosomal analysis by a conventional technique such as karyotyping can only detect aneuploidy and large segmental duplication or deletion. Newer techniques such as high-resolution microarray analysis allow for the study of alterations in chromosomal segments that are less than 5 Mb in length; this has led to identification of critical region and genes in the pathogenesis of omphalocele. Case Presentation . The current study is the initial report of a newborn male with a 15q23 gain and a giant omphalocele. High-resolution chromosomal microarray analysis identified this gain of copy number spanned 676 kb, involving almost the entire NOX5 gene (except for exon 1 of the longer transcript), the entirety of the EWSAT1, GLCE, PAQR5, KIF23, RPLP1, and DRAIC genes and exons 1–3 of the PCAT29 gene. Conclusion . To date, this is the first report of an associated 15q23 gain in a case with omphalocele. Interestingly, Giancarlo Ghiselli and Steven A Farber have reported that GLCE knockdown impairs abdominal wall closure in zebrafish. We also identified GLCE gene alteration in our case. This highlights the importance of GLCE in abdominal wall development. Further study of the function of GLCE and other genes might lead to a better understanding of the molecular mechanism of omphalocele.